Speed-dependent effects and Dicke narrowing in nitrogen-broadened oxygen. (November 2015) - Wójtewicz, S.; Masłowski, P.; Cygan, A.; Wcisło, P.; Zaborowski, M.; Piwiński, M.; Ciuryło, R.; Lisak, D.
Abstract: We present the line-shape analysis of the nitrogen-broadened P9 P9 oxygen B -band transition measured by the optical frequency comb-assisted Pound–Drever–Hall-locked frequency-stabilized cavity ring-down spectrometer. Perturbation by both oxygen and nitrogen molecules is taken into account simultaneously in the line-shape analysis. Several line-shape models describing physical effects such as Dicke narrowing, the speed dependence of collisional broadening and shifting, and the correlation between velocity- and phase-changing collisions were used in the analysis. The comparison between the hypergeometric and quadratic approximations of the speed-dependent effects is presented. Observed line narrowing is mostly determined by the speed dependence of the collisional broadening. Abstract : Highlights: Line shapes of O 2 16 B-band transition were measured. Self- and N2 -broadening line-shape parameters are given. The hypergeometric and quadratic approximations of the speed-dependent effects are compared. Line-shape parameters for the quadratic speed-dependent Nelkin-Ghatak profile (SD q NGP) are provided.